The improvement of oral communicative competence in english through the artificial intelligence: Desarrollo de la competencia comunicativa oral en inglés mediada por la inteligencia artificial - Cango Patiño, Adriana Elizabeth; Vidal Montaño, Viviana Madelaine; Cabrera Buri, Paulina Elizabeth; Abad Rojas, María Eugenia; Cabrera González, Amparo del Rocío (LATAM Revista Latinoamericana de Ciencias Sociales y Humanidades, 2024)
The study "Improvement of Oral Communicative Competence in English through the Artificial Intelligence" focused on exploring how artificial intelligence technology can influence the development of oral communication skills during the teaching and learning process of English as a second language, with the participants of this research being future teachers of the subject. This research aimed to determine the effectiveness of artificial intelligence applications, such as voice assistants and speech recognition systems, in improving students' oral communicative competence. The study examined how these artificial intelligence systems provided instant and personalized feedback, as well as opportunities for continuous oral practice for students. It also explored how artificial intelligence can adapt to the individual needs of students, which was beneficial for those with different skill levels or specific learning needs. The results of this research demonstrated that teaching and learning mediated by artificial intelligence had significant implications, suggesting how artificial intelligence technology can play an integral role in the development of oral communicative competence in English and possibly other languages. Finally, this teaching approach promises to facilitate more effective and accessible learning for a larger number of students, enhancing their oral communication skills in the process.